2015
DOI: 10.1136/archdischild-2014-307819
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical significance of cardiac murmurs in schoolchildren

Abstract: The study suggested that apparently healthy schoolchildren with grade ≤2 cardiac murmurs are least likely to have underlying SHD, especially in those aged ≥10 years. However, echocardiography should be performed in younger schoolchildren with cardiac murmur grade ≥3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Burden estimates varied subnationally, by population subgroup, data source and over time. For example, in Dongguan City, 5 of 81 213 children aged 5–13 years screened in 2011–2012 had echo-confirmed RHD, 21 equating to 0.06 per 1000. Among adults aged 18–74 years from nine communities in urban and suburban China, prevalence of echo-detected RHD was 1.86 per 1000 in 2001–2002.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Burden estimates varied subnationally, by population subgroup, data source and over time. For example, in Dongguan City, 5 of 81 213 children aged 5–13 years screened in 2011–2012 had echo-confirmed RHD, 21 equating to 0.06 per 1000. Among adults aged 18–74 years from nine communities in urban and suburban China, prevalence of echo-detected RHD was 1.86 per 1000 in 2001–2002.…”
Section: Resultsmentioning
confidence: 99%
“…In China, studies since 2000 indicate persistent burden among school children aged 5–13 years 21 and the general population aged 30 and over 29 and 18–74 years. 20 Available Chinese data were predominantly from large cities; many less developed provinces had data gaps.…”
Section: Discussionmentioning
confidence: 99%
“…However, our previous study showed that schoolchildren with the loudness of grades 3-6 and those younger than 10 years of age should raise a high index of suspicion of CHD and should refer to the echocardiographic examinations. 7 Therefore, the loudness grades of cardiac murmurs should be considered in this study. Data should be collected in the baseline clinical characteristics.…”
mentioning
confidence: 99%
“…We are surprised that this potentially important clinical characteristic has not been considered, despite the known increase in CHD risk with louder cardiac murmurs and younger age. 7 If the loudness grades of cardiac murmurs have been recorded in the study presented by Dilek Dilli and colleagues, it would have been of utmost interest to consider this factor in this study to evaluate its potential contribution to the CHD risk.…”
mentioning
confidence: 99%
“…Congenital heart disease may be diagnosed prenatally, during birth or during hospitalization; however, many cases are asymptomatic for the first days and may go undetected. It is important to remember that most murmurs are not pathological, but a murmur may be the first or only clue to consequential congenital heart disease [2,3].…”
Section: Introductionmentioning
confidence: 99%